Understanding Salmon Migration Dynamics in a Data‐Limited Environment. (12th August 2022) - Buchanan, Rebecca A.; Whitlock, Steven L.
Abstract: Effective management of natural resources and migratory fish populations depends on understanding the relationship between life cycle parameters, management decisions, and environmental conditions. However, the difficulty of data collection can result in small or nonrepresentative data sets, thus limiting the accuracy and utility of modeling results. This is especially true for studies of migratory species in changing environments. In such situations, reevaluating previous results in light of new data is an essential exercise. We used three additional years of acoustic telemetry data to assess and update previous statistical models of survival of juvenile fall‐run Chinook Salmon Oncorhynchus tshawytscha smolts emigrating through the southern portion of the Sacramento–San Joaquin River Delta (hereafter, "Delta") in California. Some previously identified relationships were maintained with the additional data, including the significance of water flow measures in areas outside the main‐stem migration route and the role of water temperature and river discharge into the system for upstream reaches. The net downstream‐directed discharge in the interior Delta was associated with fish movement to a large water pumping facility, but its perceived importance in the original analysis depended on a single dominant study year. Survival in dry years was predicted to be higher in the upstream region of the main‐stem San Joaquin River when a temporary rock barrier limited entry of fish and river flow to the first distributary encountered in the Delta. In normal and wet years, through‐Delta survival was predicted to be higher for fish that departed the main‐stem river at that distributary. However, considerable uncertainty remains in the modeling results. Additional monitoring will be necessary to further reduce uncertainty and ensure that the modeling results reflect the system as it responds to climate change.